An Improved Model Facet Method to Support EA Alignment - Jonathan Pepin; Pascal André; Christian Attiogbé; Erwan Breton (Complex Systems Informatics and Modeling Quarterly)
Information System evolution requires a well-structured Enterprise Architecture and its rigorous management. The alignment of the elements in the architecture according to various abstraction layers may contribute to the management but appropriate tools are needed. We propose improvements to the Facet technique and we develop accompanying tools to master the difficulties of the alignment of the models used to structure an Enterprise Architecture. This technique has been experimented on many real life cases to demonstrate the effectiveness of our EA alignment method. The tools are already integrated in the Eclipse EMF Facet project.